The Evaluative Aspect of Diplomatic Speeches during the UN Security Council's Meetings in 2022 - Holtseva, Maria (Studia Philologica, 2023)
The article identifies the evaluative aspect of diplomatic speeches during the UN Security Council’s meetings in 2022, which contributes to the separation of a true attitude towards the topic. That is possible to notice in discussion, information, and country, which is noted by the diplomat in his/her speech. The evaluations are subject to noticed information, facts, sources and specific individuals that have participated directly in the events mentioned in the diplomatic speeches. The connection between valorative, voluntative and modelling aspects of diplomatic speech is noted. The method of assessment includes: 1) positioning, 2) distance, 3) mythologization, 4) retrospection, which is mainly implemented through hyperbolization and ideologization. The linguistic implementation of these techniques occurs by the predominance of expressive verbalization, the involvement of stylistic means, comparison with one of the prominent figures of the past, the contrast opposition of "we-they" for more effective misleading. It is proven based on a quantitative analysis of the archival posts of the UN Security Council, which affects not only the course of discussing the current issue, but also the adoption of resolutions, taking part or not in a specific conflict, etc. In the article, preferences are provided to the explicit assessments, in particular through the use of lexical and stylistic tools. Implicitness is also found in the evaluation of diplomatic speeches, but to a lesser extent than the explicitness of the assessment. At the verbal level, the assessment is voiced either in advance of the prepared speech or as part of an additional word during the meeting; at a non-verbal level, the score is traced by a subtext invoiced by the addressee during a speech or an additional word as a reaction to what is heard during the meeting. The interaction of explicit and implicit forms of realization of valority testifies to the complex nature of diplomatic speech at the meetings of the UN Security Council. The relevance of the problem of identifying the evaluative aspect of diplomatic speeches is due to the global significance of the impact of evaluation on the course of diplomatic negotiations with further consequences at the international level.